Possible relationship between endocrine disrupting chemicals and hormone dependent gynecologic cancers. (July 2016) - Dogan, Selen; Simsek, Tayup
Abstract: The effects of the natural and synthetic estrogens have been studied for a long time but the data regarding estrogen related chemicals (endocrine disrupting chemicals, EDCs) and their effects on reproductive system are scarce. EDCs are hormone like agents that are readily present in the environment, which may alter the endocrine system of humans and animals. Approximately 800 chemicals are known or suspected to have the potential to function as EDC. Potential role of EDCs on reproductive disease has gained attention in medical literature in recent years. We hypothesize that exposure to low doses of EDCs in a chronic manner could cause hormone dependent genital cancers including ovarian and endometrial cancer. Long term exposure to low concentrations of EDCs may exert potentiation effect with each other and even with endogenous estrogens and could inhibit enzymes responsible for estrogen metabolism. Exposure time to these EDCs is essential as we have seen from Diethylstilbestrol experience. Dose–response curves of EDCs are also unpredictable. Hence mode of action of EDCs are more complex than previously thought. In the light of these controversies lower doses of EDCs in long term exposure is not harmless. Possibility of this relationship and this hypothesis merit further investigation especially through in vivo studies that could better show the realistic environmental exposure. With the confirmation of our hypothesis, possible EDCs could be identified and eliminated from general use as a public health measure.